Invite Only Dinner with Bernard Witkin at Basque Hotel - Watkins, Howard::::::::: (1986)
L to r: Judge Frank Creede, Jr. Bernard Witkin talking, Judge Robert Coyle, Jim Gregory, Judge Gene Gomes, Judge Harold Thompson, Judge Leonard Meyers, Jim Barum, Judge Jim Paige standing, Judge Milo Popovich, and Jack Baker